Cooperative Education as a Catalyst for Retaining Talented International Students in Canada: A Qualitative Exploration - Ademuyiwa, Idris; Drewery, David; Fannon, Anne-Marie (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2026)
This study explores how cooperative education (co-op) influences international students’ decisions to immigrate to Canada. Semi-structured interviews were conducted with 25 former international students who graduated from the University of Waterloo’s co-op program between 2014 and 2022. Through a thematic analysis of transcripts, we identified co-op’s impact on immigration through school-to-work transitions. Participation in co-op enhanced skill development, clarified career preferences and pathways, and strengthened professional networks, resulting in early post-graduation employment, sometimes with a previous co-op employer. Most participants reported that their Canadian employment motivated their application for permanent residency, with some altering their initial plans to return to their home countries. However, immigration intentions were moderated by perceived barriers in Canada’s immigration system, sociocultural factors, and aspirations for opportunities abroad. These findings highlight the pivotal role of co-op in supporting Canada’s talent import strategy.